The Role of Human Resource Competence in Improving the Performance of Tempe SMEs in Sidoarjo Regency - Dita Silviana; Dewi Andriani (Indonesian Journal of Cultural and Community Development, 2022)
Competence is a form of knowledge, experience, creativity, a sense of morale, and innovation that exists within a person. The purpose of this research is to analyze the role of employee competence or the competence of Human Resources (HR) in improving the performance of MSMEs. The method of determining the sample in this study is using the purposive sampling method. The data in this study were analyzed to prove the role of Human Resources (HR) competence on MSME performance. The results of this study were found for employee competence to have a role in the performance of Tempe SMEs in Podokaton Village, Jabon District, Sidoarjo. The benefit of this research is that it can add to the literature related to employee competency issues and to support previous research.